The Influence of YouTube-Based Learning on Students’ Learning Outcomes in Aqidah Akhlak at MIN 1, North Gorontalo Regency - Haidar Bilaleya; Ibnurawandi (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This study investigates the impact of YouTube-based learning on students’ motivation in Akidah Akhlak at MIN 1 North Gorontalo Regency. YouTube was selected as a learning medium due to its capability to deliver engaging visual and audio content, which is expected to enhance students’ interest and motivation. The study employed a quantitative experimental design with a purposively selected sample of students. Data were collected using a learning motivation questionnaire and classroom observation sheets. Findings reveal a significant increase in students’ learning motivation following the implementation of YouTube-based learning, indicating the effectiveness of digital media in fostering active participation and improving motivation in Akidah Akhlak learning. These results suggest that teachers can leverage digital platforms as an instructional strategy to enhance both the quality of teaching and students’ learning motivation.